The Effect of Filler on Weld Metal Structure of AA6061 Aluminum Alloy by Tungsten Inert Gas (TIG) - M., Ishak; A. S. K., Razali; N. F. M., Noordin; L. H. A., Shah; F. R. M., Romlay (Universiti Malaysia Pahang, 2015)
Innovative welding technology for joining Aluminum alloys in automobile, aviation, aerospace and marine industries would achieve weight reduction, high specific strength as well as increase the fuel efficiency and reduce the environmental pollution. This research introduced appropriate welding filler selecting to joint similar AA6061 aluminum alloys by Tungsten Inert Gas (TIG) process. TIG welding of AA6061 was butt joined with three different filler which are ER5356 (4.5-6% Mg), ER4043 (4.5-6% Si) and ER4047 (11-13% Si). The experiments are conducted in order to investigate the macrostructure and microstructure of the samples as well as mechanical properties. The effect of preheating was also investigated. The effect of different filler used on weld joint was analyzed by its visual appearance, microstructures, hardness and strength. It was found that, welding using filler ER5356 produced finer grain size at fusion zone is 25.69 µm compared to filler ER4043 and ER4047 with the grain size of 52.75 µm and 76.78 µm, respectively. ER5356 specimen also shows highest hardness value which is 72.9HV compared to ER4043 and ER4047 counterpart, which is 59.3HV and 57.6HV, respectively. As for tensile test result, the weld joints using filler ER5356 has highest strength which is 171.53 MPa compared to weld joints using ER4043 and ER4047 filler with value 167.34 MPa and 168.03 MPa, respectively. It can be concluded that TIG welding using ER5356 filler yields better joint compared to ER4043 and ER4047.